ENERGY SAVINGS THROUGH THE APPLICATION OF BUILDING INFORMATION MODELLING (BIM): A PILOT STUDY - Ahmad Firdaus; Mohd Rofdzi Abdullah; Nur Azfahani Ahmad (Journal of Islamic, Social, Economics and Development, 2021)
In order to ensure the public universities in Malaysia to achieve sustainable energyin the future, these universities should start a program of energy saving by exploring newtechnology of Building Information Modelling (BIM). Evaluation of the pre-retrofitting lightingperformances are needed to ensure an effectives energy saving for these universities throughmeasurement with the integration of BIM. As part of technical solution, this paper willinvestigate the energy performances on actual condition of existing building in a universitythrough the adoption of BIM. The aim of this research is to improve the energy performance inan existing university building with the adoption of BIM with the aim to save the energy. Energyperformance can be improve by reviewing the energy usage of many appliances in the building,importantly lighting. To achieve the objective energy performance, this university building willbe reduce the cost, increase in value and contribute more productivity sustainabilityenvironment to campus users. This paper will identify the potential strength and weaknesses ofapplying BIM through energy performance process during the pilot study. The outcome of thispaper will be used to determine the potential of BIM in the existing university building in orderto improve energy performance. Therefore, it will improve the works of the maintenancedepartment in universities to check their work through digital application that will providemore accurate energy readings.